Comparing the effect of transcranial random noise stimulation and transcranial direct current stimulation over the motor cortex on motor performance in men vs. women: a randomized controlled crossover study - Frankel, Elchanan; Friedman, Jason; Frenkel-Toledo, Silvi (Frontiers in Human Neuroscience, 2025)
Non-invasive Brain Stimulation may modulate motor function. One commonly investigated method is transcranial direct current stimulation (tDCS). In the last few years, a new stimulation technique has been developed and studied, namely transcranial random noise stimulation (tRNS). Both stimulation techniques have displayed a certain degree of inconsistency regarding their impact on motor performance. One explanation for this may be related to differences in the sex of the participants. Thirty healthy individuals (15 female) participated in a single-blind counterbalanced crossover trial. All participants received three stimulation conditions: high frequency-tRNS, tDCS, and sham stimulation. Stimulation was applied for 10 min at 1.0 mA, with a frequency range of 101–640 Hz for the tRNS. In all stimulation conditions, the anode (for tDCS) was placed over C4 and the cathode over the contralateral orbit. The participants performed a sequential reaching motor task on a digital tablet before, during, and immediately after the stimulation. Movement time, reaction time, and peak velocity did not differ between stimulation conditions. However, within-condition analyses showed improvements in movement time and peak velocity following tRNS only, while reaction time improved in all stimulation conditions. No significant effect of sex was observed. While no clear advantage for a specific stimulation condition was statistically confirmed, these within-condition effects suggest that tRNS may modestly enhance motor performance and warrant further investigation. Additionally, in this experimental setup, sex did not influence the effects of tRNS and tDCS on motor performance.